Alcohol and drug use in a sample of Brazilian Army soldiers - Suellen Cristina Chaves; Maria do Perpétuo Socorro Socorro de Sousa Nóbrega; Divane de Vargas (Universidad Nacional de Colombia, 2022)
Objective: To identify the pattern of use of alcohol and other drugs and its related sociodemographic variables in a sample of Brazilian Army soldiers. Materials and method: Cross-sectional study conducted with 229 soldiers from an infantry battalion at the Brazilian Army. Data were collected in 2019 with the application of a sociodemographic and employment instrument, the Alcohol Smoking and Substance Involvement Screening Test (ASSIST), and the Pearson correlation test. Results: The prevalence of alcohol use was present in more than half of the studied sample, followed by tobacco and cannabis sativa. Regarding the pattern of use, alcohol (22.2%), tobacco (31%), and cannabis sativa (9.7%) reported significant results. The sociodemographic variables of the individuals in the sample, their educational level (years of schooling), and economic-related issues were the main variables associated to alcohol and drug use. Conclusions: The consumption of alcohol and other drugs by the military is lower than that identified for the general population in the Brazilian territory. The use of psychoactive substances in the military context is often part of an attempt to deal with stress. Therefore, it is necessary to implement strategies aimed at preventing alcohol and drug use and promoting mental health among this population.